PENGGUNAAN BAHAN AJAR BERBASIS MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Ahmad Gufron; Darwan Darwan; Widodo Winarso (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2018)
Mathematics is a lesson that most students do not like. This, resulting in low mathematical learning outcomes. Therefore, in order to optimize the results of learning mathematics is required interactive and innovative teaching materials. The utilization of teaching materials based on interactive multimedia is an alternative solution that is needed to the problem. So the purpose of this study is to analyze the influence of the use of interactive multimedia-based teaching materials to the results of learning mathematics. The measured mathematical learning results include affective, psychomotor and cognitive spheres. The method used in this study is a qualitative research design with One-Group Pretest-Posttest Design. The study population used class VII in MTsN 8 Losari. With class study sample VII A by random sampling. Data collection was done before and after being treated which was obtained through math test, then analyzed using linear regression test. it was found that interactive multimedia usage response was in a good category with 74% percentage. In the affective domain is in the good category with a percentage of 74%. While in the psychomotor realm is in a good category by obtaining 77.5% percentage. In addition, the results of pretest (33.22) and posttest (85.84) averaged, then an increase of 44%. When viewed from hypothesis test by using regression test; 1) ineffective learning result, interactive multimedia influence 15,5%, 2) learning result of the psychomotor domain, multimedia affects 15,8%, and 3) in multimedia cognitive domain influence 11,4%. This shows that there is the influence of interactive multimedia usage to the three aspects of student learning result of mathematics